A Systemic Treatment of Families with a Child Diagnosed with Autism Spectrum Disorder Using a Narrative Lens. Issue 5 (19th October 2020) - Romney, Justin Sterling; Jones, Ethan Ryan
Abstract: Autism Spectrum Disorder (ASD) is a neurodevelopment disorder that now affects one in 59 children, a 15% increase from the 2012 report. Although there have been numerous studies on the treatment of ASD, interventions focus primarily on the individual diagnosed with ASD. Marriage and family therapists' (MFT) are in a unique position to handle the systemic dynamics of ASD. As a result, many MFTs find it difficult and outside their scope of practice to work with these families. We will explore aspects of narrative family therapy, conceptualization, and interventions, giving the reader a base understanding of how to implement narrative therapy while working with this population.